Determinants Of Organizational Performance: A Systematic Review Of Management Studies - Achmad Efendi; Agus Sanjaya; Siti Masruroh (CV Pena Jaya Pers, 2025)
Purpose:Organizational performance has become a central issue in management research due to increasing environmental complexity and competitive pressures. This study aims to systematically review and synthesize the determinants of organizational performance identified in management studies, providing an integrated understanding of key influencing factors and research trends. Design/methodology/approach:This study employs a systematic literature review by analyzing peer-reviewed journal articles indexed in reputable databases. The review follows PRISMA guidelines with clearly defined inclusion and exclusion criteria to ensure methodological rigor. Findings:The results indicate that organizational performance is primarily influenced by human resource factors, leadership, strategic capabilities, innovation, and governance mechanisms. Dynamic capabilities and employee-related variables emerge as dominant determinants across studies. Research limitations/implications:This review is limited to selected databases and publication periods, which may restrict the generalizability of findings. Practical implications:Managers can use these findings to prioritize strategic and human resource initiatives to enhance organizational performance. Originality/value:This study provides an integrative synthesis of organizational performance determinants and proposes future research directions. Paper type: Literature review